(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information on conducting practical classes in nuclear medicine using innovative educational technologies. The purpose of the educational method is explained. Together with this, the issues related to the coverage of the topic with interactive methods based on problem situations were analyzed.